Research on equity analysis and forecasting of nursing human resource allocation in Jiangxi Province, China - Yunyu Du; Zhiqin Xie; Zhen Yang; Wanyin Xiong; Li Zhou; Min Zhang; Suhua Zeng; Min Wang (International Journal of Nursing Sciences)
Objectives: This study aimed to assess the equity of nursing human resource allocation in Jiangxi Province, China, and forecast future trends in the next five years. Methods: We used the related data from the China Statistical Yearbook, China Health Statistics Yearbook, and Jiangxi Statistical Yearbook (2003–2022). The equity of nursing human resource allocation was evaluated using Lorenz curves, Gini coefficients, and Theil index, from the perspective of population and geographical area. Demands for nursing human resource in Jiangxi Province from 2023 to 2027 were forecasted using the Autoregressive Integrated Moving Average (ARIMA) and Grey (1,1) models. Results: From 2003 to 2022, all the key nursing human resource indicators continuously increased; the number of registered nurses in Jiangxi Province increased by 109,786, with an average annual growth rate of 7.80%. Registered nurses per 1,000 population rose by 2.21, while nurses per square kilometer increased by 0.66. Jiangxi Province has surpassed the national level in several nursing resource indicators, including registered nurses as a percentage of health technicians, registered nurses per square kilometer, and doctor-to-nurse ratio. Within the province, all indicators in cities are higher than those in county-level regions. Among the cities in Jiangxi Province, Ganzhou City had the highest number of registered nurses, Xinyu City led in the doctor-to-nurse ratio, and Nanchang City had the highest bed-to-nurse ratio. In 2022, the Gini coefficients for registered nurses in Jiangxi Province were 0.09 by population and 0.34 by geographical area, reflecting the allocation of registered nurses in Jiangxi Province is highly equitable by population but relatively equitable by geographical area. Forecasting results suggested that the number of registered nurses in Jiangxi Province will reach 170,100 by 2027, indicating continued growth and improvement in nursing resource allocation. Conclusions: Over the past two decades, the human nursing resources in Jiangxi Province have grown substantially. The absolute fairness of nurse human resources allocation by population highlights significant progress, although regional disparities persist. These findings provide a foundation for optimizing future nursing resource allocation to ensure equitable access to healthcare services.